Attitudes Towards Learning English Among The Aliya Madrasah Students in Bangladesh - Rahman, Abu Rashed Md Mahbuber; Jalaluddin, Ilyana; Mohd Kasim, Zalina; Darmi, Ramiza (Indonesian Journal of Applied Linguistics, 2021)
Affective variables such as attitude, autonomy, motivation, self-esteem, and anxiety are crucial among the factors that contribute to learning a second/foreign language. Among them, one of the most important factors in inspiring learners to learn a language is their attitudes towards learning. The purpose of this study was to examine the cognitive, emotional as well as behavioral attitudes of Bangladeshi Aliya madrasah students towards learning English. The study also explored the differences in their attitudes towards learning English based on demographic profiles, that is, their gender, their parents’ monthly family income, and their parents’ education level. Data were obtained via questionnaire surveys and they were analyzed quantitatively using descriptive statistics, independent T-test, and one-way ANOVA. The results revealed that the participants demonstrated highly positive cognitive, emotional, and behavioral attitudes towards learning English. The analysis also showed that there was a statistically significant difference in the students’ attitudes towards learning English based on their parents’ monthly family income and their parents’ education level. However, the results presented no significant difference in the students’ attitudes towards learning English in relation to gender. This finding may help teachers to improve their classroom preparation by understanding their students’ attitudes better and making the learning activities easier for them. Moreover, it may inform the students’ attitudes to the authorities and policymakers responsible for devising policy for madrasah education, planning curriculum and designing materials for the madrasah students.